Electroacupuncture Stimulation Regulates Adipose Lipolysis via Catecholamine Signaling Mediated by NLRP3 Suppression in Obese Rats - Lu, Mengjiang; Yu, Ziwei; Li, Qian; Gong, Meirong; An, Li; Xu, Tiancheng; Yuan, Mengqian; Liang, Chao; Yu, Zhi; Xu, Bin (Frontiers in Endocrinology, 2022)
Chronic low-grade inflammation of visceral adipose tissue can cause obesity-associated insulin resistance, leading to metabolic syndrome. However, anti-inflammatory drugs and those for obesity management can lead to serious side effects such as abnormal heart rate and blood pressure. Consequently, the aim of this study was to explored the therapeutic potential of electroacupuncture stimulation (ES) for obesity and associated chronic inflammation. Sprague-Dawley male rats were fed high fat diet (HFD) ten weeks to build obesity model, and half of the diet induced obesity (DIO) rats were received ES. The levels of inflammatory factors were detected by ELISA and qPCR analysis. The nerve-associated macrophages were marked with immunofluorescence staining. The molecular mechanism of NLRP3 inflammasome in ES was determined by NLRP3 inflammasome activation model. Compared to HDF rats, ES showed decreased body weight and chronic inflammatory damage. Specifically, this occurred via a decrease in monoamine oxidase-A (MAOA) expression, which suppressed noradrenaline degradation. MAOA is expressed in NAMs, and ES attenuated NAMs by suppressing the NLRP3 inflammasome. The NLRP3 agonist blocked the noradrenaline degradation-reducing effect of ES, and an increase in lipolysis via the inhibition of the NLRP3 inflammasome attenuated NAMs. Thus, our findings suggest that ES induced lipolysis via the NLRP3 inflammasome in nerve-associated macrophages (NAMs), independently of sympathetic nervous system activity.